Contrast enhanced ultrasound in diagnosis of endometrial carcinoma and endometrial hyperplasia - Su, Qichen; Sun, Zhen; Lv, Guorong (Cellular and Molecular Biology, 2018)
The present study was aimed to compare application of contrast enhanced ultrasound (CEUS) in diagnosis of endometrial carcinoma (EC) and endometrial hyperplasia (EH). A total of 81 patients with EC and simple EH were selected in this study. Among all patients, 39 cases were diagnosed as EC and 42 cases were diagnosed with EH. All patients were diagnosed by CEUS examination. The diagnosis of EC and EH was also confirmed by endometrial biopsy. CEUS was conducted for all patients. Eendometrial thickness was measured and the mean arrival time, time-to-peak, enhancement time, arrival intensity, peak intensity, enhancement intensity, rising rate, washout half-time and clearance half-time were recorded. Myometrial invasion was categorized into 2 stages <50% and >50%. No significant difference was observed in clinical basis between the two groups. Endometrial thickness of EC was significantly higher than that of EH, P<0.05. Results of CEUS parameters showed that in EC patients, all values of arrival time, time-to-peak, washout half-time and clearance half-time were all shorter in EC group compared with those in EH patients, P<0.05. And values of peak intensity, enhancement intensity, and rising rate were also lower in EC patients than those in EH patients, P<0.05. Diagnostic accuracy of CEUS in myometrial invasion for EC was shown showed that 26 of 30 cases were diagnosed as myometrial invasion <50% by CEUS and 7 of 9 cases were diagnosed as myometrial invasion >50%. The total diagnostic accuracy of CEUS is 82.62% (33/39). We conducted a comparison study to analyze different diagnostic effects of CEUS for EC and EH. The study may give more clinical basic data in the field of CEUS application in diagnosis of EC and can give a reference to the difference between EC and EH.